Moltmann"s theology in dialogue with liberation theologians revives the role of Black Theology in democratic South Africa - Resane, Kelebogile T. (HTS teologiese studies, 2021)
The theme for Liberation Theology has always been about concerns for the marginalised masses and socio-political liberation for the economically disadvantaged. Its mandate is to seek to guide towards the discovery of being human without references to historical divisions between the haves and have-nots created by socio-economic imbalances promoted by political regimes. Moltmann’s content of theology, its revision, its innovation rather than the theological method has marked his restless imagination. His method of exploration in doing theology has brought him into dialogue with philosophers and theologians of different persuasions. In this study, he is evaluated in his dialogue with the liberation theologians. The focus is on Moltmann’s theological approach to ecumenism, built around the Kingdom of God concept, and ecclesiastical analysis and political theology. These three areas are the transitional arguments on how Moltmann enters into dialogue with the liberation theologians. The argument moves on to point how Liberation Theology has exerted itself as Black Theology in South Africa during the apartheid time. Black Theology is a theology of liberation because of its resistance and endeavours of eradication of all forms of oppressive systems. The two injustices (socio-cultural misnomers) in the democratic South Africa are discussed as a calling for Black Theology’s voice. These are corruption and human rights abuses. Black Theology brings religion into the secular world as a way of aborting all forms of discrimination based on race, sex and economic class.Contribution: Black Theology is invited to revisit Moltmann’s ecumenical, ecclesiastical and political theological understanding, as a way of reviving itself back to the centre stage of prophetic role within the corrupt and human rights and dignity abuse society.